PENGARUH KONDISI EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS 1 DI SDN 3 MANGARAN KABUPATEN SITUBONDO - Eko Hadi Purwanto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Parent's economic condition is a reality that is seen or felt by the human senses about the state of parents and the ability of parents to meet their needs. Parental economic conditions are one of the external factors of the emergence of motivation to continue children's education. Motivation will provide an encouragement or enthusiasm to behave in carrying out activities for someone to achieve a desired goal, without motivation, the activities of one's life will decrease. The diversity of parents' economic background can also affect achievement abilities more precisely on children's learning motivation, so that economic conditions are one of the factors that determine the success of children's education. Most of the parents of students of class 1 SDN 3 Mangaran are in middle to lower economic condition and based on the curriculum vitae of grade 1 students that researchers saw when conducting preliminary surveys, livelihoods from parents of 1st grade students as traders, farm laborers, and civil servants. The number of parents of students who work as farm laborers is 15 people, traders are 6 people, and civil servants are 1 person. In addition, information from class 1 teachers that stationery (pencils, erasers, rulers) and notebooks and drawing books used in teaching and learning activities are incomplete. This study aims to determine the effect of parents' economic level on learning motivation of 1st grade students at Mangaran Elementary School 3 Situbondo District. This research was conducted at SDN 3 Mangaran Situbondo District Class 1. The research method used was non-experimental method. The sample of this study included 22 grade 1 students at SDN 3 Mangaran. The research instrument consists of 20 questionnaires / questionnaires with four answer choices. Questionnaire validity is calculated using biserial point correlation formula. The questionnaire reliability coefficient is 0.973 for parents' economic condition questionnaire and 0.974 for this learning motivation questionnaire is calculated by the KR 20 formula. This is evidenced by looking at the price of t, where t count:6.897> t table: 1.725, so Ha is accepted that there is a significant effect economic conditions of students towards the learning motivation of grade 1 students at SD Negeri 3 Mangaran, Mangaran District, Situbondo Regency